1978
DOI: 10.1192/s0007125000283372
|View full text |Cite
|
Sign up to set email alerts
|

The Patient and the First Psychiatric Interview

Abstract: SummaryThis paper presents work that formed the basis of a fourth-year project at Southampton University Medical School. Thirty patients were seen prior to their first psychiatric consultation and asked about their hopes, fears and expectations. Twenty-five were seen subsequently.The study, which is largely descriptive, shows that many patients have unrealistic expectations about various aspects of the interview, and afterwards many are dissatisfied with its outcome. The paper discusses these findings and make… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1979
1979
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…We must agree with Michaels and Sevitt (1978) when they recommend that general practitioners should spend more time explaining what to expect in psychiatric out-patients at the time of referral. This problem of lack of communication between doctor and patients is highlighted in Reynolds' (1978) study of surgical patients at another Bristol hospital.…”
Section: Commentsmentioning
confidence: 99%
See 1 more Smart Citation
“…We must agree with Michaels and Sevitt (1978) when they recommend that general practitioners should spend more time explaining what to expect in psychiatric out-patients at the time of referral. This problem of lack of communication between doctor and patients is highlighted in Reynolds' (1978) study of surgical patients at another Bristol hospital.…”
Section: Commentsmentioning
confidence: 99%
“…It would appear, therefore, that for most patients they are not a serious inhibition to the interview. Michaels and Sevitt (1978), in a study on the first psychiatric interview, found that many patients were inhibited in the interview for various reasons unconnected with students. The present teaching method, with two or three students sitting in the consulting room with the doctor seems satisfactory, both in terms of practicality and patient acceptance.…”
Section: Commentsmentioning
confidence: 99%